Integrasi Augmented Reality dan Etnomatematika: Inovasi Media Pembelajaran Interaktif Materi Bangun Ruang - Sulisti, Hidayu; Zulkarnain, Zulkarnain; Septianawati, Desty; Suprianto, Agus; Setyaningrum, Vidya; Aditya, Farninda (PIONIR: JURNAL PENDIDIKAN, 2026)
The purpose of this study is to develop an interactive learning medium based on Augmented Reality (AR) and ethnomathematics for fifth-grade solid geometry at MIN 2 Pontianak, as well as to determine the validity and practicality of the developed medium. This study falls under the category of Research and Development (R&D), utilizing the 4D development model. The data sources for this study were fifth-grade teachers and students at MIN 2 Pontianak. Data collection techniques included interviews using a structured interview instrument as well as questionnaires consisting of a validity questionnaire and a practicality questionnaire. Data analysis techniques included validity analysis and practicality analysis. Based on the research results, during the definition phase, it was found that students require interactive visual media connected to the local cultural context. The design phase resulted in an AR-based media design that integrates traditional buildings such as the Pontianak Grand Mosque and the Radangk House to visualize the structures of cubes and blocks. The development phase demonstrated that this media is highly valid and practical, with a practicality score of 82.2%. During the dissemination phase, the media was distributed in the form of digital links via WhatsApp. Overall, this media is considered suitable for use because it effectively combines technology, culture, and students’ learning needs. Keywords: Media Development, Augmented Reality, Ethnomathematics, Spatial Construction